Humeral fractures by arm wrestling in adult: a biomechanical study - Pedrazzini, A.; Pedrazzoni, M.; De Filippo, et al., M. (Acta Biomedica Atenei Parmensis, 2012)
Humeral shaft fractures may occur as a result of arm wrestling. We discuss the biomechanics of this rare injury mechanism. Using Strength of materials concepts, Computerized Tomography and Bone Density Scans we studied the biomechanical and anatomical conditions that predispose to this particular fracture. An unfavorable ratio between inner-outer diameter and a low bone mineral concentration in the distal third of humerus compared to other sections of bone were seen as critical aspects. The biomechanical study observed the primary importance of these factors to explain the typical shape and location of this fracture. These results indicate that each arm wrestler should be conscious of the risks of practicing this activity.